Faktor-Faktor Penentu Efektivitas Audit Internal: Peran Pengalaman, Independensi, Dukungan Manajemen, dan Etika Auditor - Dian Safitri Amelyana; Christina Christina (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2026)
This research endeavors to examine the impact of auditor experience, independence, management support, and auditor ethics on the efficacy of internal audits at PT GMD Indonesia. The inclusion of auditor ethics as an additional variable distinguishes this study from prior research. The methodological framework employed is a quantitative approach, focusing on the population of internal auditors within the company. A sample comprising 52 respondents was selected utilizing purposive sampling techniques. Data analysis was conducted through multiple linear regression, incorporating the F test, t test, and coefficient of determination. The findings indicated that, when analyzed collectively, all four variables exerted a significant influence on the effectiveness of internal audits. In contrast, when analyzed individually, only auditor ethics demonstrated a significant impact, whereas auditor experience, independence, and management support did not show a significant effect. The coefficient of determination reveals that 54.3% of the variability in internal audit effectiveness can be elucidated by the four aforementioned variables, while the remaining variance is attributed to extraneous factors not encompassed within this study.